Integrative Therapies in Cancer: Modulating a Broad Spectrum of Targets for Cancer Management. (March 2015) - Block, Keith I.; Block, Penny B.; Gyllenhaal, Charlotte
Integrative medicine is an approach to health and healing that "makes use of all appropriate therapeutic approaches, health care professionals, and disciplines to achieve optimal health and healing." A comprehensive integrative medicine intervention for cancer patients typically includes nutritional counseling, biobehavioral strategies, and promotion of physical activity, as well as dietary supplements including herbs, nutraceuticals, and phytochemicals. A broad-spectrum intervention of this type may contribute uniquely to improvement in cancer outcomes through its impact on a wide variety of relevant molecular targets, including effects on multiple cancer hallmarks. Hallmarks that may be particularly affected include genetic instability, tumor-promoting inflammation, deregulated metabolism, and immune system evasion. Because of their susceptibility to manipulation by diet, exercise, and supplementation, these may be characterized as metabolic hallmarks. Research on the use of comprehensive integrative approaches can contribute to the development of systems of multitargeted treatment regimens and would help clarify the combined effect of these approaches on cancer outcomes.